Application of heat pump drying technology to produce dried mango products from Tu Quy mango (Mangifera india L.), Vietnam, on a pilot scale - Thao, Bui Thi Thu; Thanh Hung, Pham; Lai, Ngoc Dung; Tran, Thi Yen Nhi; Nguyen, Ngoc Quy; Pham, Tri Nhut; Truc Tran, Thanh; Giang Bach, Long; Dao, Tan Phat (Frontiers in Sustainable Food Systems, 2024)
In this study, the heat pump drying technique was applied to develop the production process of dried mango from Tu Quy mango sources, Ben Tre province, Vietnam. The experiment was performed in three steps. First, mango slices were treated through the blanching process. Samples were pretreated with sizes from 6 to 12 mm at 80–95°C for 3–6 min, and then the mango slices were soaked in a syrup solution concentration range of 25–40°Bx, citric acid of 0.5–2%, and glycerol of 0.1–0.4% at 35–65°C for 90–180 min. Finally, the samples were dried using a pilot-scale heat pump dryer until the moisture content reached 14–16%. The results showed that the blanching and osmosis processes were carried out under optimal conditions to inactivate the Polyphenol oxidase (PPO) enzyme, obtain maximum polyphenol compounds, and conform to the product appearance. Additionally, the drying process was carried out at 30°C for 1,080 min with the polyphenol content retaining 11.71 mgGAE/gDW—This signifies a successful endeavor in developing production methodologies and expanding the range of mango-derived products. Employing innovative technological processes enhances both the quantity and quality of the products. Moreover, the manufacturing procedure was executed on a pilot device, streamlining the synchronization of large-scale production processes effortlessly. This advancement not only enhances economic value but also addresses the issue of congestion prevalent in the current state of the mango industry in Vietnam.